Memories of Revolution: Zur Deutungsgeschichte einer Revolution (Sansibar 1964) - Loimeier, Roman (Africa Spectrum, 2006)
Keywords: Zanzibar

In His (Arab) Majesty's Service : The Career of a Somali Scholar and Diplomat in Nineteenth-Century Zanzibar - Hoffman, Valerie J. (The global worlds of the Swahili: interfaces of Islam, identity and space in 19th and 20th century East Africa, 2006)
Keywords: Zanzibar

Soqotra: South Arabia's Strategic Gateway and Symbolic Playground - Elie, Serge D. (British Journal of Middle Eastern Studies, 2006)
This article undertakes a critical retrospective of the symbolic appropriation process through which Soqotra was constituted as an imaginative geography, embodying the strategic desiderata of states as well as the ideational fantasies of men over millennia. The island’s location on the threshold of continents (Africa and Arabia), and on a cardinal node on the sea-lanes linking the Indian Ocean to the Red Sea and beyond, subjected its internal dynamics to the maelstrom of events in the larger world. Moreover, its physical isolation endowed it with an endemic biodiversity that has spurred reveries about the lost Garden of Eden, and made it a coveted haven for a mosaic of human aspirations. The article examines the strategic interests pursued, and the appropriating discourses deployed, by the European powers vying for political and economic hegemony at the different historical periods surveyed here: Antiquity, Portuguese, British, Soviet and the recent adoption of a United Nations-brokered environmental regime for Soqotra. Finally, it draws out the ramiﬁcations of this strategic entanglement and symbolic appropriation process on Soqotra’s estimated 50,000 inhabitants at the present historical conjuncture.
Keywords: Zanzibar

Possedere Zanzibar. Riflessioni sulle politiche di ‘controllo’ nell’oceano Indiano occidentale durante il XIX secolo - Nicolini, Beatrice (Palaver, 2006)
At the coast of equatorial Africa, divided from the mainland for a channel width of only thirty miles, lies the island of Zanzibar (Unguja). The regular recurrence of the monsoon allowed to continue contacts with India, the Red Sea and the Gulf, the proximity of the coast represented a strategic position for trade between the interior of Africa and the Indian Ocean, Zanzibar was in the nineteenth considered 'the depot of the richest trade in Eastern Africa'. Special opportunities for trade in goods and slaves, controlled by the Omani dynasty of Al Bu Sa'id, could not escape the political and commercial interests of France and England.
Keywords: Zanzibar

Sansibar und die Deutschen: ein besonderes Verhältnis ; 1844 - 1966 - Schneppen, Heinz (Europa - Übersee, 2006)
Keywords: Zanzibar

Donne di Zanzibar. Percezione della realtà femminile attraverso gli ngoma - Brunotti, Irene (Africana: Rivista di Studi Extraeuropei, 2006)
Keywords: Zanzibar

The Makran-Baluch-African Network in Zanzibar and East Africa during the XIXth Century - Nicolini, Beatrice (African and Asian Studies, 2006)
Keywords: Zanzibar

The Legacy of Bishop Frank Weston of Zanzibar 1871-1924 in the Global South Anglicanism - Byaruhanga, Christopher (Exchange, 2006)
Abstract The idea of comprehensiveness, which I call 'facing-both-ways' in matters of faith, is unknown, at least for now, in the Global South Anglicanism where the Anglican Church is used to preaching the Gospel plainly and unmistakably. The story of homosexuality in the Anglican Communion came to the spotlight at the 1998 Lambeth Conference, at which the Anglican bishops of the Global South of the Anglican Communion emerged as the most prominent opponents of any form of approval of homosexual practice by the Anglican Church. By asking the hard question as Bishop Frank Weston of Zanzibar did in 1913: Anglican Communion: For What Should She Stand? Anglican bishops of the Global South of the Anglican Communion drew the Communion's attention to the place and role of Global South Anglicanism in the Communion and World Christianity.
Keywords: Zanzibar